Reference values for the incremental shuttle walk test in patients with cardiovascular disease entering exercise-based cardiac rehabilitation. Issue 1 (2nd January 2017) - Cardoso, Fernando M.F.; Almodhy, Meshal; Pepera, Garyfalia; Stasinopoulos, Dimitrios M.; Sandercock, Gavin R.H.
ABSTRACT: The incremental shuttle walk test (ISWT) is used to assess functional capacity of patients entering cardiac rehabilitation. Factors such as age and sex account for a proportion of the variance in test performance in healthy individuals but there are no reference values for patients with cardiovascular disease. The aim of this study was to produce reference values for the ISWT. Participants were n  = 548 patients referred to outpatient cardiac rehabilitation who underwent a clinical examination and performed the ISWT. We used regression to identify predictors of performance and produced centile values using the generalised additive model for location, scale and shape model. Men walked significantly further than women (395 ± 165 vs. 269 ± 118 m; t  = 9.5, P   < 0.001) so data were analysed separately by sex. Age (years) was the strongest predictor of performance in men ( β = −5 .9; 95% CI: −7.1 to −4.6 m) and women ( β  = −4.8; 95% CI: −6.3 to 3.3). Centile curves demonstrated a broadly linear decrease in expected ISWT values in males (25–85 years) and a more curvilinear trend in females. Patients entering cardiac rehabilitation present with highly heterogeneous ISWT values. Much of the variance in performance can be explained by patients' age and sex. Comparing absolute values with age-and sex-specific reference values may aid interpretation of ISWT performance during initial patient assessment at entry to cardiac rehabilitation.